Failure in International Business and Entrepreneurship : Literature review on definition of failure and its causes - Leimu, Ann-Sofie (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2018)
Every business either succeeds or fails during time. Nevertheless, failure research has received far less attention than business successes, even though studying failures represents an essential research field since it may help us understand why they occur and even develop practices to avoid them. Additionally, failure is a complex and multifaceted term, which can be difficult to define without misinterpretations. There exists multiple related and synonymous terms for it, which causes even more confusion and obscurity. It is also shown that statistics regarding business failures can be biased due to different perspectives and interpretations of the phenomenon. The aim of this thesis is to define failure in international business and entrepreneurship literature, and study other terminology related to it as well. Secondly, the aim is on studying the most relevant causes of failure from environmental, organizational and individual perspectives. For the purpose of the research, a broad literature review was conducted. The existing academic literature was analysed to form a wide understanding of the subject. The literature was searched from multiple databases and focused on academic journals published in English and between the years 1975 and 2017. Based on the research, failure is defined as termination of a business (or a unit) due to its’ inability to reach goals for whatever reason and thereby failing to satisfy stakeholders’ expectations. Failure is a dynamic set of actions and consequences that can be attached to de-internationalization, exit, divestment and withdrawal, and resulting the organization to cease activity in some extent or completely. Additionally, it is clear that causes of failure rise from either external environment or from internal factors. Failure has been studied from various perspectives, all giving a different emphasis on the causes. However, there does not seem to exist proper models on forecasting a failure, nor to avoid them completely. Nevertheless, even though failure is one of the most devastating and complicated business phenomena for both individual and organization, it can also be seen as a beneficial learning experience. The research shows, however, that academic literature is definitely lagging behind in properly studying the concept of failure. There are strong proof that there exists vagueness and indecisiveness causes remarkable trouble in defining main terminology, operationalizing the concept, classifying the subject and even collecting proper statistics on the matter. Therefore, there still exist an urgent need to standardize and harmonize existing knowledge by agreeing on a common terminology and by setting commonly agreed ground rules on the subject.